Screening for premature coronary artery disease (CAD) using coronary artery calcium (CAC) score: a primary prevention pilot study - Mohd Ruslan M,; Mohd Shawal FM,; Norzailin AB,; Shathiskumar G,; Tiau, WJ; Oteh M,; Hamat Hamdi Che Hassan, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Acute Coronary Syndrome (ACS) events can be accelerated by positive family history of young coronary artery disease (CAD). Risk factors assessment sometimes fail to predict ACS occurrence. Additional investigations with coronary artery calcium (CAC) score can be used independently in screening for primary prevention in some population. This was a cross-sectional study in asymptomatic population with first degree relatives (FDR) having premature CAD compared with a matched population with no family history of CAD from September 2017 to March 2018 at the Cardiology Clinic of Univeristi Kebangsaan Malaysia Medical Centre. A total of 36 subjects were recruited with equal number in each group. Female were the majority in each group (66.7%). The FDR group were slightly younger compared to the control group [mean (SD) age 36.9 (4.9) against 38 (3.8), respectively). Both groups represent high risk factors including overweight and obesity, abdominal obesity as well as dyslipidemia. Newly diagnosed dyslipidemia was significant in the group with family history (83.3% versus 44.4%, P<0.01). Both groups were screened either into the low or moderate risk Framingham Risk Score group. CAC score was higher in family history group (11.1% vs 0%, P>0.05). In conclusion, CAC may be irrelevant for screening in younger population. However, the yield of other risk factor is still alarming.